The Alexander Technique For Actors - McEvenue, Kelly (Performance Bks., 2016)
Kelly McEvenue teaches the Alexander Technique, a method of physical relaxation that reduces tension throughout the body. This guide to the technique is specially adapted for actors to promote efficient use of the body. The book includes a series of step-by-step warm-ups and exercises.